Evolution of Liability of Content Sharing Platform Providers and Other Intermediary Service Providers for Copyright Infringement - Anikó Grad-Gyenge (Public Governance, Administration and Finances Law Review)
The study examines the changing liability regime for intermediary service providers. It analyses the rules introduced by the CDSM Directive for content sharing platform providers, before contextualising these rules within the Digital Services Act (DSA) and reviews the changes in terms of liability for copyright infringement of other intermediary service providers. Finally, the paper considers the extent to which the DSA complements the new liability regime set out in the CDSM Directive.